Usage of animations as advertising tools / Baderisang Mohamed and Malawanis Mohd Noor Kama - Mohamed, Baderisang; Mohd Noor Kamal, Malawanis (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
The latest technology application and current trend of marketing have influenced the usage of animation in the product advertising (Callcott & Lee, 2013). The word ‘animation’ comes from the Latin word ‘animate’ and means to bring life to or to invoke life. It is the process of creating the illusion of movemen t brought by sequencing either 2D drawings or computer generated images or 3D objects such as clay or plasticine (Chitchyan, 2011) Therefore, animation is defined as a series sequence of static images to create the illusion of movement. Most people believe the creation of real pictures or individual images is an animation, but according to the author it is the disposition of static images that conveys the movement (Thant, 2008). The animation gives free expression to the imagination (Goel & Upadhyay, 2017).